Colored Overlays: An Intervention Tool in Reading for the Grade Two Learners - Geonzon, Tiffany Ivana (JPAIR Multidisciplinary Research, 2019)
Reading is a foundation skill that plays a major role in a child’s academic success. It is also an ability that unlocks the door of learning and success. At the same time, reading can be very challenging, especially when the materials are unfamiliar, technical, and complex. The researcher thought of a material that could alleviate reading difficulties particularly the reading rate of the learners. This material is called Color Overlays. It is a type of tinted filter and is a plastic reading sheet tinted with color and placed over text to eliminate a wide range of reading difficulties such as low reading rate, accuracy, and comprehension. This research investigated the effects of Irlen’s Colored Overlays on reading rate as an intervention tool for the Grade Two Instructional Level of learners, with a class teacher initiating the study and a teacher-librarian conducting the assessment. All of the 52 learners were screened with a vision test. They were grouped into two wherein only the experimental group used the color overlays as their intervention. The result of the study implies that with or without the intervention, the reading rate of the learners is expected to increase. Therefore, color overlays made a difference in improving the reading rate of the learners.